Implementasi Algoritma Hue Saturation Value (HSV) Pada Penentuan Kualitas Beras Berbasis Android - Yuliana Aprilia Anwar; Billy Eden William Asrul; Sitti Zuhriyah (Ikatan Ahli Informatika Indonesia, 2023)
Rice is the staple food of most Indonesian people. Rice contributes more than 22% of global energy intake. Indonesia, especially South Sulawesi is a major rice producer where rice production is around 92% of total world production 1.2 For nations in Asia. This research aims to implement the Hue Saturation Value (HSV) algorithm for extracting color features in Android-based rice quality determination. In this research there were 600 images of rice which were divided into 80% training data and 20% testing data. Training samples are used for color feature extraction by applying Red, Green and Blue (RGB) features to the Hue Saturation Value (HSV) method. Next, image identification is carried out to determine the quality of the rice using color features. From the test results using the confusion matrix at a value of K=7, precision was 82%, recall was 90%, F-1 score was 86%, and accuracy was 85%